PERAN MEDIASI E-SATISFACTION DAN E-TRUST TERHADAP E-LOYALTY - Rayi Retno Dwi Asih; Luki Adiati Pratomo (Jurnal Manajemen dan Pemasaran Jasa, 2018)
As the number of female customers shopping in online clothing stores increases, understanding how female customers’ e-loyalty is formed and fostered in this type of online store becomes very important. The purpose of this paper is to focus on female online clothing shoppers and to examine the mediating of e-loyalty in the context of online clothing stores: e-satisfaction and e-trust. The number  of respondents is 196 persons who have online clothing shopping experience in Jakarta. The structural equation modeling was performed to analyze the measurement and structural models. The results show that both Online Satisfaction and Online Security are positively associated with e-trust, whereas web design is not. Furthermore, Online Satisfaction turns positively influence e-loyalty for female online clothing shoppers.